Upaya Meningkatkan Hasil Belajar PKN Siswa Menggunakan Strategi Pemetaan Informasi Di Kelas V Sdn 07/III Sungai Abu - Pidarsi S.Pd (STKIP Pesisir Selatan, 2016)
Abstract The problems to be examined in this study is: Does the use of information mapping strategies to improve learning outcomes Civics fifth grade students of SDN 07 / III River Abu? The purpose of this action research was to determine students' learning outcome Civics using information mapping strategies in class V SDN 07 / III River Abu. This study uses classroom action research as much as two rounds. Each round consists of four phases: planning, implementation, observation and reflection. Goal of this study was to determine students' learning outcome Civics using information mapping strategies in class V SDN 07 / III River Abu. The data obtained are quantitative and qualitative data. From the analysis it can be seen that through the use of information mapping strategies have a positive impact in improving student learning outcomes Civics characterized by increased mastery learning students in each cycle, the first cycle (63.50%), the second cycle (78.50%).Keywords: Strategy mapping information, learning outcomes, PKn.